Grapevine Grafting: Scion Transcript Profiling and Defense-Related Metabolites Induced by Rootstocks - Chitarra, Walter; Perrone, Irene; Avanzato, Carla G.; Minio, Andrea; Boccacci, Paolo; Santini, Deborah; Gilardi, Giovanna; Siciliano, Ilenia; Gullino, Maria L.; Delledonne, Massimo; Mannini, Franco; Gambino, Giorgio (Frontiers in Plant Science, 2017)
Rootstocks are among the main factors that influence grape development as well as fruit and wine composition. In this work, rootstock/scion interactions were studied using transcriptomic and metabolic approaches on leaves of the ‘Gaglioppo’ variety, grafted onto 13 different rootstocks growing in the same vineyard. The whole leaf transcriptome of ‘Gaglioppo’ grafted onto five selected rootstocks showed high variability in gene expression. In particular, significant modulation of transcripts linked to primary and secondary metabolism was observed. Interestingly, genes and metabolites involved in defense responses (e.g. stilbenes and defense genes) were strongly activated particularly in the GAG-41B combination, characterized in addition by the down-regulation of abscisic acid (ABA) metabolism. On the contrary, the leaves of ‘Gaglioppo’ grafted onto 1103 Paulsen showed an opposite regulations of those transcripts and metabolites, together with the greater sensitivity to downy mildew in a preliminary in vitro assay. This study carried out an extensive transcriptomic analysis of rootstock effects on scion leaves, helping to unravel this complex interaction and suggesting an interesting correlation among constitutive stilbenes, ABA compound and disease susceptibility to a fungal pathogen.